Penerapan Metode SQ3R (Survey, Question, Read, Recite, Review) untuk Meningkatkan Aktivitas dan Hasil Belajar Biologi Siswa Kelas VIIIA SMP Negeri 1 Lamuru Kabupaten Bone - . Syamsiah; . Adnan; . Suhriana (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFClassroom action research aims to improving the students' activities and biology learning outcomes through the application of SQ3R (Survey, Question, Read, Recite, Review) method. The subjects were students of VIIIA class at SMP Negeri 1 Lamuru, semester I, 2011/2012 academic years, consisted of 24 students, 13 male and 11 female. The research was carried out into two cycles. Collected data of learning outcomes were analyzed by using quantitative analysis. The results showed that the application of SQ3R method could improve the students' activities and biology learning outcomes. The improvements were shown by findings from cycle I to cycle II, namely: (1) the students' activities showed improvement in asking, reading, finding the pictures from the whole materials, and mentioning the answers, (2) the students' learning outcomes improved from the average score in cycle I was 63.19 to 74.86 in cycle II. In addition, improvement also occurred in a number of the students in mastery learning which in cycle 1 was 41.67% and in cycle II was 83.33%. Based on the findings, it could be concluded that the implementation of SQ3R method improved the students' activities and biology learning outcomes of VIIIA class at SMP Negeri 1 Lamuru. Key words: Learning activity, learning outcomes, SQ3R method